Manipulating turn residues on de novo designed β-hairpin peptides for selectivity against drug-resistant bacteria. (November 2021) - Tram, Nhan D.T.; Selvarajan, Vanitha; Boags, Alister; Mukherjee, Devika; Marzinek, Jan K.; Cheng, Bernadette; Jiang, Zi-Chen; Goh, Pascal; Koh, Jun-Jie; Teo, Jeanette W.P.; Bond, Peter J.; Ee, Pui Lai Rachel
Abstract: Synthetic β-hairpin antimicrobial peptides (AMPs) offer a useful source for the development of novel antimicrobial agents. β-hairpin peptides generally consist of two side strands bridged by a reverse turn. In literature, most studies focused on the modifications of the side strands to manipulate the stability and activity of β-hairpin peptides, and much less is known about the impact of the turn region. By designing a series of de novo β-hairpin peptides with identical side strands but varied turns, we demonstrated that mutations of only 2 to 4 amino acids at the turn region could impart a wide range of antimicrobial profiles among synthetic β-hairpin AMPs. BTT2–4 and BTT6 displayed selective potency against Gram-negative bacteria, with minimum inhibitory concentrations (MICs) of 4–8 µM. In contrast, BTT1 exhibited broad-spectrum activity, with MICs of 4–8 µM against both Gram-positive and Gram-negative strains. Additionally, BTT1 was potent against methicillin-resistant Staphylococcus aureus (MRSA) and colistin-resistant Enterobacterales . The antimicrobial potency of BTT1 persisted after 14 days of serial passage. Mechanistic studies revealed that interactions between lipopolysaccharide (LPS) and the peptides were critical to their membranolytic activity against the bacterial inner membrane. Aside from folding stability, we observed that a degree of conformational flexibility was required for disruptive membrane interactions. Statement of significance: By examining the significance of the turn region of β-hairpin peptides, we present valuable knowledge to the design toolkit of novel antimicrobial peptides as alternative therapeutics to overcome antibiotic resistance. Our de novo designed synthetic peptides displayed selective activity against Gram-negative bacteria and potent activity against clinically relevant antibiotic-resistant strains (e.g. colistin-resistant Enterobacterales and methicillin-resistant Staphylococcus aureus ). The bactericidal activity of our peptides was shown to be robust in the presence of proteolytic trypsin and saline, conditions that could suppress peptide activity. Our peptides were also determined to be non-cytotoxic against a human cell line. Graphical abstract: Image, graphical abstract